Hydrodynamic effects on particle deposition in microchannel flows at elevated temperatures - Yang, Chun (2019)
Particulate fouling and particle deposition at elevated temperature are crucial issues in microchannel heat exchangers. In this work, a microfluidic system was designed to examine the hydrodynamic effects on the deposition of microparticles in a microchannel flow, which simulate particle deposits in microscale heat exchangers. The deposition rates of microparticles were measured in two typical types of flow, a steady flow and a pulsatile flow. Under a given elevated solution temperature and electrolyte concentration of the particle dispersion in the tested flow rate range, the dimensionless particle deposition rate (Sherwood number) was found to decrease with the Reynolds number of the steady flow and reach a plateau for the Reynolds number beyond 0.091. Based on the Derjaguin–Landau–Verwey–Overbeek (DLVO) theory, a mass transport model was developed with considering temperature dependence of the particle deposition at elevated temperatures. The modeling results can reasonably capture our experimental observations. Moreover, the experimental results of the pulsatile flow revealed that the particle deposition rate in the microchannel can be mitigated by increasing the frequency of pulsation within a low-frequency region. Our findings are expected to provide a better understanding of thermally driven particulate fouling as well as to provide useful information for design and operation of microchannel heat exchangers.